Educational strategies in the resolution of school conflict among adolescents - Remache-Bunci, Manuel (2023)
The purpose of the research was, on the one hand, to establish the relationship between the variables that make up the components of conflict, strategies and coexistence actions; on the other hand, determine the actions of coexistence, more akin to the strategies used by teachers. Due to the nature of school coexistence, students interact with positive and negative attitudes, provoking behaviors and conflicts of different nature and intensity. Therefore, the role of teachers is to generate solutions to conflicts. The research design was quantitative and descriptive with a non-experimental correlational level. The objects under review were the students from ninth and tenth grade of Basic General Education in the city of Quito. The instrument for data collection was the survey, it was structured according to the variables, dimensions and indicators. The data processing was carried out with the support of the SPSS software and the results allowed: to answer the research questions, Is there a linear relationship between the components conflicts, strategies and coexistence actions? What are the coexistence actions that are most related to the strategies used by teachers in conflict resolution? it concludes with, the existence of a relationship between the conflict components, strategies and actions of coexistence. According to the perception of those surveyed, the strategies most used by teachers were to make the approach to conflict resolution viable; while the coexistence actions with the greatest relationship were: the participation of students and teachers in the establishment of norms, expression and regulation of emotions, work within the class curriculum, education in values, cooperation in class activities, due to the significance established in the results